The Effect of N/P Ratio on the In Vitro and In Vivo Interaction Properties of PEGylated Poly[2-(dimethylamino)ethyl methacrylate]-Based siRNA Complexes - Gary, Dana J.; Min, Jungbin; Kim, Youngwook; Park, Keunchil; Won, You-Yeon (WILEY-V C H VERLAG GMBH, 2013)
PEG-PnBA-PDMAEMA triblock and PEG-PDMAEMA diblock copolymers are used as model systems for studying the role of N/P ratio on the in vivo behavior of PEGylated siRNA carriers in mice. The presence of a free/uncomplexed polymer population coexisting with siRNA complexes is established. A change in the N/P ratio exerts no significant influence on the in vivo biodistribution and ex vivo blood chemistry properties of the respective systems. Histological analysis of major organs indicates that the presence of uncomplexed polymer elicits toxicity to the organ that is associated with the clearance of the siRNA complexes from the circulation system. This effect can be eliminated by working at N/P ratios near the charge-neutralization point of the complexes.
Keywords: GEL ELECTROPHORESIS; POLYAMIDOAMINE DENDRIMERS; POLYMERIC MICELLES; DIBLOCK COPOLYMER; GENE TRANSFECTION; MOLECULAR-WEIGHT; FREE POLYCATIONS; DELIVERY; BIODISTRIBUTION; POLYPLEXES